(untitled) - Jurkovicova, Hana (Doprava a spoje, 2012)
At present the important issue is fares in public transport. The article is about the public transport fares in selected towns of the Slovak Republic. The paper deals with comparing the amount of selected tourism in selected cities. The paper also deals with evaluation analysis.